Vitamin K antagonists and cardiovascular calcification: A systematic review and meta-analysis - Kosciuszek, Nina D.; Kalta, Daniel; Singh, Mohnish; Savinova, Olga V. (Frontiers in Cardiovascular Medicine, 2022)
Background: Many patients treated with Vitamin K antagonists (VKA) for anticoagulation have concomitant vascular or valvular calcification. This meta-analysis aimed to evaluate a hypothesis that vascular and valvular calcification is a side-effect of VKA treatment. Methods: We conducted a systematic literature search to identify studies that reported vascular or valvular calcification in patients treated with VKA. The associations between VKA use and calcification were analyzed with random-effects inverse variance models and reported as odds ratios (OR) and 95% confidence intervals [95%CI]. In addition, univariate meta-regression analyses were utilized to identify any effect moderators. Results: Thirty-five studies were included (45,757 patients; 6,251 VKA users). The median follow-up was 2.3 years (interquartile range [IQR] of 1.2 - 4.0); age 66.2 ± 3.6 years (mean ± SD); the majority of participants were males (77% [IQR: 72%-95%]). VKA use was associated with an increased OR for coronary artery calcification (1.21 [1.08, 1.36], p=0.001), moderated by the duration of treatment (meta-regression coefficient B of 0.08 [0.03, 0.13], p=0.0005). Extra-coronary calcification affecting the aorta, carotid artery, breast artery, and arteries of lower extremities, was also increased in VKA treated patients (1.86 [1.43, 2.42], p<0.00001) and moderated by the author-reported statistical adjustments of the effect estimates (B: -0.63 [-1.19, -0.08], p=0.016). The effect of VKA on the aortic valve calcification was significant (3.07 [1.90, 4.96], p<0.00001); however, these studies suffered from a high risk of publication bias. Conclusion: Vascular and valvular calcification are potential side effects of VKA. The clinical significance of these side effects on cardiovascular outcomes deserves further investigation.